Analysis Of Primary Health Care Activity Through The Integrated Health Program (Pis) In Ermera Municipality, Year 2025 - Levi Anatolia S.M. Exposto; Aniceto da Conceição Pacheco; Marilia Juvi Goncalves; Honoria de F. P. Carvalho; Marcos Carvalho (Riviera Publishing, 2025)
The distribution of health services is every effort carried out individually or collectively in an organization to maintain and improve health, prevent and cure diseases and restore the health of individuals, families, groups and communities. The study purpose to find out the primary health care activity through integrated health program in Ermera Municipality. The study used a qualitative descriptive method. The research was conducted at Sub-district 6 in Ermera District. Sample was 1287 heads of families in Ermera Municipality. Technical Analysis uses descriptive statistics. The results show that all citizens in Ermera have equal rights when undergoing treatment at the Health Post; those who do not make good progress for their health will continue to undergo treatment /health care at the Community Health Center. According to results, 90.4% of Ermera Municipality said “Yes” and 9.6% said “No”. Based on Post Administrative respondents said “Yes” 93.9% from Railaco, 94.9% from Letefoho, 70.9% from Hatólia B, 58.8% from Hatólia A, 95.7% from Ermera Vila, 97.9% from Atsabe. And some respondents answered “No” 41.2% from Hatolia A and 29.1% from Hatolia B is 29.1%, and Railaco is 6.1%. The study highlights the importance of Primary Health Care Activity through Integrated Health Program. Recommends to the Ermera municipal health service, the Ministry of Health and relevant parties to use the results of this research to make decisions and health interventions for society.